Math, asked by ridro, 2 months ago

2/5x-3/8+1/16+3/5×-3/8​

Answers

Answered by purrnendushekharsen
1

Step-by-step explanation:

 \frac{2}{5} x -  \frac{3}{8}  +  \frac{1}{16} +  \frac{3}{5}  \times  -  \frac{3}{8}  \\ =   \frac{2}{5} x -  \frac{3}{8}  +  \frac{1}{16} +  ( - \frac{9}{40} ) \\  =  \frac{2}{5} x -  \frac{3}{8}  +  \frac{1}{16}  -  \frac{9}{40}  \\  = \frac{2}{5} x -  (\frac{3 \times 2}{8 \times 2}  +  \frac{1}{16})  -  \frac{9}{40}  \\  = \frac{2}{5} x -  (\frac{6}{16}  +  \frac{1}{16})  -  \frac{9}{40} \\  = \frac{2}{5} x -   \frac{7}{16}   -  \frac{9}{40} \\ =  \frac{2}{5} x -  \frac{7 \times 5}{16 \times 5}  -  \frac{9 \times 2}{40 \times 2}  \\  =  \frac{2}{5} x -  \frac{30}{80}  -  \frac{18}{8}  \\  =  \frac{2}{5} x

Similar questions